A price-at-risk approach for the German commercial real estate market - Tobias Herbst; Jannick Plaasch; Florian Stammwitz (Deutsche Bundesbank, 2024)
We apply the growth-at-risk model of Adrian et al. (2019) to the German commercial real estate (CRE) market. We derive a distribution for CRE price growth four quarters ahead conditional on macro-financial variables. This approach allows us to make probability statements about the downside risk to future CRE price growth, which serve as an input to financial stability analyses. We find that the conditional distribution has shifted strongly to the left since the COVID-19 pandemic, in line with deteriorating macroeconomic conditions, an increase in long-term interest rates and a decline in the net initial yield, resulting in lower expected CRE price growth rates across the entire distribution.
Keywords: C32; E37; G01; R33; 330; Commercial Real Estate; Quantile Regression; Growth-at-Risk; Germany